2010
DOI: 10.1111/j.1540-8175.2009.00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Ultrasound Speckle Tracking Imaging in Evaluation of Early Changes in Left Ventricular Diastolic Function in Patients with Essential Hypertension

Abstract: STI may be helpful for the detection of early changes in left ventricular diastolic function in patients with EH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 28 publications
(37 reference statements)
3
21
0
1
Order By: Relevance
“…Park et al 50 observed that both torsion and recoil were significantly increased in individuals with grade 1 diastolic dysfunction, when compared with healthy volunteers and patients with grades 2 and 3 diastolic dysfunction. Other studies showed reduction in the recoil rate and in the longitudinal strain velocity that precede alterations in systolic function evaluated by global longitudinal strain and LVEF 51,52 .…”
Section: Clinical Applicationsmentioning
confidence: 90%
“…Park et al 50 observed that both torsion and recoil were significantly increased in individuals with grade 1 diastolic dysfunction, when compared with healthy volunteers and patients with grades 2 and 3 diastolic dysfunction. Other studies showed reduction in the recoil rate and in the longitudinal strain velocity that precede alterations in systolic function evaluated by global longitudinal strain and LVEF 51,52 .…”
Section: Clinical Applicationsmentioning
confidence: 90%
“…This technique permits the detection of early LV diastolic function changes in hypertension, 33 and also reveals that, in hypertensive patients free from clinical manifestations of HF, the earliest myocardial impairment involves the longitudinal fibers. This technique permits the detection of early LV diastolic function changes in hypertension, 33 and also reveals that, in hypertensive patients free from clinical manifestations of HF, the earliest myocardial impairment involves the longitudinal fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Redukcija ranog dijastolnog SR takođe ide sa globalnim promenama dijastolnog punjenja i ukazuje na oštećenu relaksaciju miokarda leve komore. 17,18,19 Cilj istraživanja je bio da se ispitaju mogućnosti strain imaging ehokardiografije u analizi segmentne sistolne i dijastolne funkcije kod pacijenata sa novootkrivenom hipertenzijom, i da se utvrdi primenjivost nove metode u rutinskoj kliničkoj praksi.…”
Section: Slikaunclassified